Phase diagrams and stoichiometries of the solid electrolytes, Bi 4V2O11: M, M = Co, Cu, Zn, Ca, Sr - Chnoong, Kheng Lee; Goik, See Lim; West, Anthony R. (Royal Society of Chemistry, 1994)
The compositional ranges of Bi4V2O11 solid solutions containing Co, Cu, Zn, Ca and Sr have been determined by means of a phase diagram study at solidus temperatures. Depending on the size of the divalent cation, at least three and probably four mechanisms for accommodating variable cation content have been identified. These are: V ⇌ Bi, V ⇌ M, Bi ⇌ M and probably, formation of interstitial M. Most previous studies have focused on the single mechanism V ⇌ M whereas, in fact, the solid solutions are shown to be far more varied and extensive than previously supposed.